Diseño de un Dispositivo para el Aprendizaje Significativo de la Astronomía para Niños de 6 A 8 años a través de una instalación interactiva para el planetario en movimiento - Silva Merchán, Andrés David (Universidad Antonio Nariño, 2023)
Project based on promoting the learning of Astronomy through meaningful learning with topics related to the theories of physics applied to everyday life, focused on children aged 6 to 8 who are attending to the Planetarium museum of Bogotá “planetario en movimiento”. Together with the Industrial design the development of an interactive installation that allows children to learn in a fun way knowledge about the photoelectric effect and its applications.